Periodized training for high performance rugby player - Marsh, D.; Heazlewood, I. T. (7th World Congress on Science and Football (WCSF), 2011, 2011)
High performance Rugby players are in Australian representative and Super 15 Rugby teams. Super15 Rugby is played from mid-February to early July in 2011 and players are expected to perform at their best each week. The following periodization of physical and skill training has been designed for optimal Rugby specific fitness. Pre-Season and In-Season Periodization Model Pre-season consists of 10.5 weeks general physical preparation phase prior to end of December, then 1.5 weeks active rest and 6 weeks leading into first game, including trials. In-season phase is 21 weeks, including finals. Pre-season consists of 4 week blocks (3 week load/1 week unload) using a Bompa[1,2] periodization model of progressive overloading (adaptation) and unloading (restoration) phases. In-season consists of 3 week blocks (2 week load/1 week unload) as this allows for more unloading in-season to enhance recovery from games. The in-season training will be influenced by travel schedule and turnaround days between games, where a 6 day turnaround will become a lighter week with less sessions performed in this week. High intensity days are alternated with higher volume or regeneration days. Weekends are rest days to offset amount of weekends taken up with games in season and to ensure a higher quality Monday workout. The goal of the physical preparation program is to enhance expression of the players` skills. Physical factors are developed within a training block with only the emphasis within the block changing from cycle to cycle. Speed development is based on two sessions per week in pre-season focusing on technical development, high speed running (acceleration and maximum velocity) and strength and power (field and gym work). Strength is based on four sessions per week in preseason with a split of lower and upper body training, with an introductory period to strengthen ligaments and tendons and to prepare for higher intensity phases, An accumulation blocks is used to increase muscle cross-sectional area, which is correlated with strength. General conditioning is based on two sessions per week in pre-season and players split into those needing greater aerobic or anaerobic conditioning. Monitoring training response is based on the following tests; 20-40m sprints, repeat speed (12 x 20m on 20sec), Yo-Yo, 1.2km time trial, strength and power tests. Training volume is measured via GPS and response to training is measured by PRE`s and self-report indicators of wellbeing such as sleep, energy and muscle soreness.